Keraton Tertua : Keraton kesepuhan Cirebon - Akifah Tukhfatul, Athfal (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
This research aims to provide information to readers about what objects and buildings are in the Cirebon Sepuhan palace as well as the meaning, function and myths of the buildings and objects in the palace. The research method used in this study uses a qualitative descriptive research method, namely a research method used to examine the condition of natural objects as well as to explore and examine more deeply the meaning, function and myths of the oldest palace, namely the Kasepuhan Palace, Cirebon. Data collection was carried out in this research through primary and secondary data, namely data obtained from informants based on the results of interviews with tour guides while touring the Kasepuhan Palace, field observations carried out by visiting the Kasepuhan Palace, and documentation, namely notes on information or objective conditions of the research location. which was researched by recording all data directly from informants who discussed the research object and photographing buildings, inscriptions and historical objects there. Then using secondary data in the form of journal articles and relevant internet data. The results of this research are that Cirebon is an area that is rich in culture and history, such as customs that are still preserved and well preserved by the people, and also buildings that contain a long history still stand strong and are well maintained. The Cirebon Kesepuhan Palace is still preserved today so that people outside can still freely enjoy and learn the meaning of each building and heritage objects in the palace.